Considerations on the admissibility of state aid in the EU − interpretation problems of public funds transfer - Podsiadło, Piotr (Rozważania o dopuszczalności pomocy publicznej w UE − problemy interpretacyjne transferu środków publicznych, 2020)
The purpose of the article is to analyse the admissibility of granting state aid in the European Union from the perspective of meeting the Treaty condition for the use of public resources. The category “granted by a Member State or through state resources”, involves two different tests, which have been only further developed and specified in the most recent case law. Unfortunately, the case law and legal commentaries have not always drawn a clear distinction between these two levels. Firstly, it is necessary to ascertain whether the measure is “imputable” to the Member State. The second part of the double test involves ascertaining whether the measure in question leads to a burden on the state budget. This criterion too derives from the language of Article 107 par. 1 of the Treaty on the Functioning of the European Union (TFEU) and the necessity of restricting the definition of the term “State aid”. This division will be maintained to the extent in this paper
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 174-182
Keywords: European Union; imputability; member states; state aid; state resource; Unia Europejska; przypisywalność; państwa członkowskie; pomoc publiczna; środki publiczne